Plantlets Regeneration from Crown Bud Slicing of Pineapple (Ananas comosus) - Zulkarnain Zulkarnain; Neliyati Neliyati; Eliyanti Eliyanti (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
Pineapple propagation by lateral shoots, suckers or crowns is often confronted with limited number of regenerated seedlings and high diversity in flowering and fruit formation. In order to solve this problem, this study offer an alternative method by using tissue culture techniques. This study aimed to determine the effect of growth regulators on plantlet regeneration from bud slicing of pineapple cv. Tangkit. Four levels of 2.4-D (0.0, 0.001, 0.01 and 0.1 ppm) in combination with BA (0.0, 0.1, 1.0 and 10.0 ppm) were tested on solid MS medium. Cultures were incubated in total darkness for a week followed by transfer to 16-hour photoperiod. Results showed that explants treated with 2,4-D and/or BA succeeded in regenerating adventitious shoots. Average leaf number did not differ significantly among treatments (P = 0.60). Highest leaf number (2.99 ± 0.23) was obtained on medium with 0.01 ppm 2,4-D without BA, followed by 0.1 ppm 2,4-D without BA (2.85 ± 0.33). Meanwhile, roots were only formed on medium with 0.1 ppm 2.4-D without BA (4.2 ± 0.37 per shoot). Thus, complete plantlets were regenerated only on medium supplemented with 0.1 ppm 2,4-D without BA. The growth of plantlets was relatively uniform, and plantlet acclimatization succeeded 100% on Jiffy pots. The finding of optimum concentration of 2.4-D and BA in this study is important to develop standard protocol for in vitro propagation of pineapple cv. Tangkit. Thus, the benefit of producing seeds in large quantities and relatively uniform in growth is made possible through tissue culture technique.